2001
DOI: 10.1109/63.923760
|View full text |Cite
|
Sign up to set email alerts
|

Generation control circuit for photovoltaic modules

Abstract: Photovoltaic modules must generally be connected in series in order to produce the voltage required to efficiently drive an inverter. However, if even a very small part of photovoltaic module (PV module) is prevented from receiving light, the generation power of the PV module is decreased disproportionately. This greater than expected decrease occurs because PV modules which do not receive adequate light cannot operate on the normal operating point, but rather operate as loads. As a result, the total power fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
146
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(148 citation statements)
references
References 4 publications
0
146
0
2
Order By: Relevance
“…Half bridge with GCC [34] is based on a half-bridge inverter with two more additional transistors, which makes it possible the independent maximum power point tracking of the photovoltaic strings [35]. A schematic of this topology is depicted in Fig.…”
Section: Half H-bridge With Generation Control Circuit (Gcc)mentioning
confidence: 99%
“…Half bridge with GCC [34] is based on a half-bridge inverter with two more additional transistors, which makes it possible the independent maximum power point tracking of the photovoltaic strings [35]. A schematic of this topology is depicted in Fig.…”
Section: Half H-bridge With Generation Control Circuit (Gcc)mentioning
confidence: 99%
“…A photovoltaic panel is developed by connecting many solar cells in series and parallel. A single photovoltaic cell can be modeled by utilizing current source, diode and two resistors as shown in Figure 1 [10] [11].…”
Section: Modeling Of Solar Cellmentioning
confidence: 99%
“…Although tests have shown that this approach results in more power output than in the directly connected PV sources, the cluster which generates the least power will be bypassed completely. The third scheme, named the 'Generation Control Circuit' (GCC), uses a type of multilevel DC/DC converter with multiple DC/DC converters connected in series, each powered by a PV source [8]. The individual converter may be a buck-boost type and can be controlled to extract power from the PV sources and deliver it to the load directly.…”
Section: Introductionmentioning
confidence: 99%